Choroid Plexus Carcinomas With TP53 Germline Mutations: Management and Outcome - Li, Yanong; Liu, Hailong; Li, Tandy; Feng, Jin; He, Yanjiao; Chen, Li; Li, Chunde; Qiu, Xiaoguang (Frontiers in Oncology, 2021)
Abstract Background: Choroid plexus carcinomas (CPCs) are rare pediatric tumors commonly associated with Li-Fraumeni syndrome (LFS), which involves a germline mutation of the tumor suppressor gene TP53. Materials and Methods: We retrospectively analyzed the corresponding information of 12 cases, including the effects of surgery and radiotherapy and TP53 germline mutations, to analyse the management strategies. Kaplan-Meier curves and the log-rank test were used to evaluate the progression-free survival (PFS). Results: Twelve CPC patients were included, of which TP53 germline mutations were found in eight cases. All patients underwent surgical resection, and six patients received radiotherapy following with operation after initial diagnosis, one patient received radiotherapy following relapse. It was significantly different (P=0.012 and 0.028) that patients with TP53 germline mutation receiving the gross total resection (GTR) without radiotherapy showed survival advantages. Without TP53 germline mutations also showed survival advantages, but there is no statistical significance (P=0.063) Conclusions: These findings provide evidence for the therapeutic strategy that radiotherapy should not be considered for patients with TP53 germline mutations.